Polysaccharide-based nanobiomaterials as controlled release systems for tissue engineering applications - Rodríguez-Velázquez, Eustolia (2015)
Polysaccharides belong to a special class of biopolymers that has been used in different areas of research and technology for some years now. They present distinctive features attractive for the biomedical field. Among others, as extracted from natural sources, these materials are usually biocompatible and possess a significant ability to absorb water. Moreover, they can be conveniently modified by chemical means so as to display improved biological and physicochemical properties. The last but not the least, they are abundant in the natural Extracellular Matrix (ECM) and have a tremendous affinity for different endogenous macromolecules. Accordingly, these particular materials constitute outstanding candidates for a variety of biomimetic approaches entailing the entrapment/stabilization of bioactive molecules (e.g. growth factors, siRNA, and DNA) that could be delivered and have an effect on relevant cellular mechanisms, such as gene expression and cell viability, -proliferation, and -differentiation. This review will explore the current status of nano-scale drug delivery devices based on polysaccharides that could be used in tissue engineering and regenerative medicine (TERM). Aiming to contextualize the topics here discussed, especially for non-experts in the field, section 1 (Introduction) will present a brief overview of TERM and the principal polysaccharides herein employed. In order to get a broader perspective on both issues, this section will include a brief description of non-nanometric systems with relevant characteristics for TERM, such as injectable microparticles and macroscopic hydrogels, just to cite a few. Section 2 will illustrate the contributions of nanotechnology to the development of TERM, in particular to the development of biomimetic systems capable of replicating the natural, endogenous ECMs. Next, sections 3 to 6 will describe representative systems in the nanometric scale presenting 0D (nanoparticles), 1D (nanorods and nanowires), 2D (thin coatings/films or multilayered systems), and 3D (woven nanofibrillar mats and meshes) configurations, respectively. Special attention will be paid on how nanometric constructs with these configurations can be used as model systems in TERM to understand and/or manipulate biological functions at the cellular level. Finally, section 7 will provide an outlook on future perspectives in the field. Overall, the review is intended to constitute a critical source of information relative to the current status of polysaccharide- based biomaterials for TERM, in particular those at the nanometric scale.